ABOUT THE INFLUENCE OF RELIGION ON THE FORMATION OF TOLERATED CONSCIOUSNESS AND SOCIAL CONSENT - Saparov B. Zh.; Tashkyn Akhmet (Scientific Journal of Pedagogy and Economics, 2019)
The problem of tolerance demands the analysis of the nature of tolerance. Researchers connect emergence of the idea of tolerance with the period of the Reformation and the ideas of Education of the new European liberal political philosophy. The idea of tolerance, which has three hundred years old, arose for release of religions, proclaimed the liberal tradition. There are three main periods of the development: the first period is connected with the rationalistic doctrine of John Lock. At the heart of his views is the relation of belief and reason of understanding of the tolerance. The toleration, in accordance with Lock’s rational need, meansfreedom. The second period is connected with the development of perspective of tolerance in the liberal theory of John Stuart Mill. He proclaimed the idea of freedom of the individual, which can be limited only the freedom of other person. Considering problems of justice, equality as bases of the society research scholarsexplained by the need of the contract. The tolerance is one of the justice conditions, when the person has to sacrifice own beliefs for the prevailing of the rights of other members. The tolerance is approved as life style of the western society, where the person has real rights and freedoms. Traditional society is proclaimed as fundamentalist society, where the individual cannot have culture and freedom.